2020
DOI: 10.1038/s41598-020-72883-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Co concentration on properties of NiO film by sparking under uniform magnetic field

Abstract: Nickel oxide (NiO) films cover numerous electronic applications, including transparent conducting oxides and hole transport layer, because of its high transparency and wide band gap. A sparking discharge is a new and unique method for the deposition of NiO films due to non-complex operation and non-requirement of a vacuum atmosphere. Unfortunately, NiO films by the sparking method display a porous surface with inferior crystallinity. By assisting a uniform magnetic field in the sparking method, the porous and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Interestingly, this result was not in accordance with our previous work, which indicated that an increase in the magnetic eld reduced the porosity of the NiO lm. 14,15 The reason for this result was the earlier oxidation of Fe particles without annealing, which resulted in misalignment of the particles. 12 The crystal structure of Fe 2 O 3 lms analyzed by XRD is displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, this result was not in accordance with our previous work, which indicated that an increase in the magnetic eld reduced the porosity of the NiO lm. 14,15 The reason for this result was the earlier oxidation of Fe particles without annealing, which resulted in misalignment of the particles. 12 The crystal structure of Fe 2 O 3 lms analyzed by XRD is displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Published by the Royal Society of Chemistry collect more particles. To reveal the inuence of the magnetic eld on the bandgap (E g ) of Fe 2 O 3 , we used Tauc's relationship, as determined by the following equation: 14,15 (ahn) ¼ A(hn À E g ) n…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we aim to synthesize novel Cu-Fe oxides composite lms by a one-step sparking process. This process has been developed in our lab which can prepare small, uniform particles, high porous lms, and determine the composite ratio [18][19][20][21][22][23][24][25][26]. Moreover, the sparking process requires neither complicated steps nor special equipment, cheap, fast, and non-toxic.…”
Section: Introductionmentioning
confidence: 99%